Potensi Bibit Sotong untuk Pengembangan Keragaman Budidaya Nelayan Kecil sebagai Strategi Konsevasi Lamun di Perairan Pesisir Lombok Timur - Abdul Syukur; Agil Al-Idrus; Lalu Muhammad Imam Husaini M. Nasir; Pahmi Pahmi (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
Diversification of marine culture has an effective value for the sustainability of the livelihoods of small fishermen. In addition it can play a role in preventing the threat of utilization that is not environmentally friendly. Cuttlefish is one of the types of marine biota commodity that has high economic value and has the potential to be developed as a fishery diversification community. The purpose of this study was to determine the indicators of the potential of cuttlefish cultivation as a diversification strategy for small fishermen's cultivation and seagrass conservation in the study location. The research method used is the method of direct observation and interviews. Data analysis uses descriptive statistical analysis. The results showed that the average cuttlefish seedlings were 1293.5 individuals / month and the average cuttlefish caught by fishermen landed at TPI Tanjung Luar was 1229 individuals / month consisting of three species namely Sepia latimanus, Sepia pharaonis and Sepioteuthis lessoniana. In addition, marine cultivation has developed into the choice of livelihood for small fishermen, although it is still complementary. Furthermore, the group of farmers plays an active role in preventing local threats from uses that are not environmentally friendly. The conclusion is the diversification of cultivation with cuttlefish community is of strategic value to overcome the problem of the sustainability of small fishing livelihoods and local scale seagrass conservation in the study location. Therefore, diversification of cuttlefish culture can be considered, especially at the scale of small fishermen as a policy of developing seafood products to achieve food security, both at local, regional and national scale.